Pemanfaatan Open Broadcast Software Studio dan Youtube Live Streaming sebagai Media Pembelajaran IPS Kelas 9 SMP Negeri 2 Panggang - Nicolaus Adi Fusan Tara; Gunawan Sridiyatmiko (Proceedings Series on Social Sciences & Humanities, 2022)
The Covid-19 virus is the beginning of a new face change in the world, one of the sectors affected is the education sector. The new policy is provided through the Ministry of Education and Culture in the form of distance learning. Students should study at home, and under the supervision of the teacher. Online communication is one of the keys for keeping educational programs running well. Therefore, this becomes a new challenge by a the teachers to provide interesting learning and according to the characteristics of students. Through this research, it is hoped that it can provide insight to readers, especially educators, in designing innovative learning during a pandemic based on Open Broadcast Software and Youtube Live Streaming applications. In addition, this application also makes it easier for students to participate in learning, both in real time and recording. The research method used a literature study, using a qualitative descriptive approach, by collecting several previous research results from articles and journals related to the topic of this article and through direct observation of student learning in class. The results show that the interactive video learning model based on the OBS application and Youtube Live Streaming can make learning more interesting and effective, especially for most students with audio-visual learning styles. Teachers can use OBS and Youtube Live Streaming to design distance learning more effectively.